Analisis Penerapan Standar Pelayanan Kefarmasian di Puskesmas Paduraksa Kecamatan Pemalang - Fitria Dwi Alvianingrum; Musa Fitri Fathkiya (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Pharmaceutical services are carried out to achieve definite results in improving the quality of life of patients in the form of direct and resposibels services related to pharmaceutical preparations. In implementing pharmaceutical services, health centers already have a standard that is used as a guideline in its implementation. The consequences of implementing pharmaceutical services that do not comply with standards are medication errors and inappropriate use of drugs, there are expired drugs and overlapping budgets. The purpose of this study was to analyze the implementation of pharmaceutical service standards in health centers, BMHP and clinical pharmacy services based on PMK No. 74 of 2016 at the Paduraksa Health Center, Pemalang District. This study is a non-experimental study with a descriptive design that will provide an analytical description of the implementation of pharmaceutical service standards at the Paduraksa Health Center, Pemalang District based on the guidelines in the Minister of Health Regulation Number 74 of 2016. The population and sample in this study were all pharmaceutical personnel who were responsible for managing pharmaceutical service standards at the Paduraksa Health Center, by conducting interviews in the form of questions and answers by giving questions verbally to pharmacists or pharmaceutical personnel at the Paduraksa Health Center, Pemalang Regency. The data in the variable analysis looked at the percentage of compliance with standards based on the Minister of Health Regulation No. 74 of 2016.